Instilling The Value of Religious Moderation in Preventing Radicalism at The Ma'had Madinatul Ma Madinatul Khairaat Buntuna Islamic Boarding School - Maolana Maolana (Eduvest - Journal of Universal Studies, 2024)
Religious radicalism is one of the threats to the harmony of society and the state. Islamic boarding schools as Islamic educational institutions have an important role in preventing the spread of radical ideology through moderate education. This study was conducted to understand how the process of instilling the values of religious moderation takes place in this Islamic boarding school and its effectiveness in preventing radicalism among students. This study uses a qualitative research method with a case study approach. The data collection technique in this study is through literature studies and document studies. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The results of the study show that Pesantren Ma'had Madinatul Khairaat Buntuna emphasizes the importance of moderate education with an approach that teaches students to respect differences, both among fellow Muslims and with adherents of other religions. Values such as tolerance, deliberation, and brotherhood are instilled through various religious activities, such as religious studies, discussions, and social activities outside the pesantren. Students are also taught to understand religious teachings as a whole, not only from a narrow literal perspective, so that they are able to ward off radicalism.